Studies in the analysis of steel: electroanalytical determination of silicon and iron and colorimetric determination of boron - Alukaino A. Osakwe (1976)
A study has been made of the suitability for steelworks chemical analysis of two instruments recently introduced by the Princeton Applied Research Corporation, by developing some new analytical applications of these instruments. Two procedures have been developed for the determination of silicon by differential pulse polarography using a PAR 174 Polarographic Analyzer. Both procedures are based on the reduction of β-12-molybdosilicate. The heteropoly acid is formed in the presence of methyl ethyl ketone and excess of molybdate is masked with citrate. Methyl ethyl ketone also stabilises the β-12-molybdosilicate and prevents its transformation to α-12-molybdosilicate. The first method was developed for determining silicon at levels above 0.02 μg.mlˉ¹. The formation of β-12-molybdosilicate at this level takes about 15 to 20 minutes. The second method was developed for determining nanogram amounts of silicon. [Continues.]